Heat shock protein coinducers with no effect on protein denaturation specifically modulate the membrane lipid phase - Török, Zsolt (The National Academy of Sciences, 2003)
The hydroxylamine derivative bimoclomol (BM) has been shown to activate natural cytoprotective homeostatic responses by enhancing the capability of cells to cope with various pathophysiological conditions. It exerts its effect in synergy with low levels of stress to induce the synthesis of members of major stress protein families. We show here that the presence of BM does not influence protein denaturation in the cells. BM and its derivatives selectively interact with acidic lipids and modulate their thermal and dynamic properties. BM acts as a membrane fluidizer at normal temperature, but it is a highly efficient membrane stabilizer, inhibiting the bilayer–nonbilayer phase transitions during severe heat shock. We suggest that BM and the related compounds modify those domains of membrane lipids where the thermally or chemically induced perturbation of lipid phase is sensed and transduced into a cellular signal, leading to enhanced activation of heat shock genes. BM may be a prototype for clinically safe membrane-interacting drug candidates that rebalance the level and composition of heat shock proteins.